Institutional Conflict Resolution Strategies and Lecturers Productivity in Public Colleges of Education in Southwestern Nigeria - OKE, Adebowale (Ilorin Journal of Education, 2025)
Lecturer Productivity (LP) in the area of Research Output (RO) of lecturers is vital to institutional goal attainment, and could be hampered if conflicts are not properly handled. Reports have shown that LP is low in public Colleges of Education (CoEs) in southwestern Nigeria, partly due to conflict-riddled environment. Previous studies on LP focused largely on welfare schemes, manpower development and work environment, with little emphasis on Institutional Conflict Resolution Strategies (ICRS). Therefore, this study examined ICRS (Collective Bargaining, Collaboration and Dialogue) as correlates of lecturer RO in public CoEs in southwestern Nigeria The study adopted descriptive survey research design. Three states (Oyo, Lagos and Osun), which have more than one public CoE (federal and state each), were purposively selected. The eight public CoEs in the three states were enumerated. Proportionate-to-size sampling was used to select 1023 lecturers. The instrument used was ICRS Questionnaire and coefficient value of reliability was 0.80. Data were analysed using descriptive statistics and linear regression at0.05 level of significance. Lecturer RO in CoE journals (x̅=3.29) was the highest, followed by university journals (x̅=1.38) and foreign publications (x̅=0.64). CB (( x) ̅=3.91), collaboration(x ̅=3.87), were high against the threshold of 3.0. The ICRs decrease RO (β = -0.346, P >0.05). All elements of ICRS influenced lecturer research output in public colleges of education in southwestern Nigeria. Therefore, efforts should be made to avoid conflicts. Lecturers should continue to publish their research in local publications, university-based journals and international journals.